Análise espacial da cobertura vegetal do perímetro urbano de Cuiabá - MT - Arruda, Joelson Cardozo de (2023)
The spatial and functional structure of the urban perimeter in terms of vegetation is addressed as “Urban Forest”, a term introduced to address urban forests. In the urban environment, the fragmentation of forests, that is, the discontinuity of vegetation, generates unstable habitats, resulting from different degrees of anthropic disturbances. The historical process guided the form of land use and occupation without any planning in the city of Cuiabá-Mato Grosso. The general objective of this research is to map and quantify the existing vegetation cover in the urban perimeter of Cuiabá-MT, using remote sensing and Geographic Information System tools - GIS. The research is justified by the need to quantify the urban forest, using the behavior of the Normalized Difference Vegatation Index (NDVI), as well as the generation of thematic maps, to subsidize information to be included in the Municipal Master Plan and in the Master Plan for Urban Afforestation. The research has an applied and descriptive nature. For the identification of the urban forest, the selection of images from the Landsat-8 satellite of the spatial database of the Geological Survey of the United States - USGS was performed. parameters and methodologies of the Brazilian Institute of Geography and Statistics (IBGE). The results show that the supervised classification by likelihood resulted in a mapping with an acceptable reliability index, with 77% being a “strong” level. The urban perimeter of Cuiabá has 26.63% of vegetation cover, a higher value than other cities, the south region of the capital was the one that presented the largest area with 31.97% of vegetation cover, the smallest was the north region with 16, 82%, the distribution of these areas is not uniform and does not comply with relevant legislation and UN guidelines, which advocate access for all to green areas. Changes in the processes of occupation and expansion of the urban perimeter must be proposed based on guidelines for the protection, preservation and recovery of urban forests in Cuiabá.